Impact of processing conditions and sizing on the thermomechanical and morphological properties of polypropylene/carbon fiber composites fabricated by material extrusion additive manufacturing. Issue 16 (5th November 2020) - Savandaiah, Chethan; Maurer, Julia; Gall, Markus; Haider, Andreas; Steinbichler, Georg; Sapkota, Janak
Abstract: For the 3D printed composites, fiber alignment is affected by the direction of melt‐flow during extrusion of filaments and subsequently through the printing nozzle. The resulting fibers orientation and the fiber‐matrix compatibility have a direct correlation with mechanical properties. This study investigates the impact of processing conditions on the state of the carbon fiber types and their orientation on the mechanical properties of 3D‐printed composites. Short and long carbon fibers were used as starting reinforcing materials, and the state of fibers at the beginning and on the printed parts were evaluated. Strong anisotropy in terms of mechanical properties (flexural and impact properties) was observed for the samples printed with different printing orientations. Interestingly, the number of voids in the printed composites was found to be correlated with the fiber types. The present work provides a step towards the optimization of tailored composite properties by additive manufacturing. Abstract :